IMPLEMENTASI STRATEGI PERSUASIF HALLIDAY DALAM BROSUR IKLAN HOTEL HORISON (THE IMPLEMENTATION OF HALLIDAY’S PERSUASIVE STRATEGY ON HORISON HOTEL’S ADVERTISEMENT BROCHURES) - Ayi Sofyan (Metalingua: Jurnal Penelitian Bahasa, 2020)
Persuasive is one of language strategies. In a brochure, apart from paralinguistic elements, linguistic choices that include lexical choices and syntactic choices have the potentiality to change the behavior of a person. This writing focuses on how the relational process influences a person’s decision making. The method used in this study is a descriptive analytical method supported by Halliday’s theoretical approach. The results show that (1) the relationship of being on the verbal relational process contains the notion of class and entity that triggers the emotion of the person; (2) the idea of being related intensively, possessively, or merely situational; (3) the verbal relational process contains propositions that represent presentation strategies AbstrakSalah satu strategi dalam berbahasa adalah strategi persuasif. Dalam sebuah brosur,selain unsur paralinguistik, pilihan linguistik yang meliputi pilihan leksikal dan pilihan sintaktis berpotensi mengubah perilaku pesapa. Kajian ini memfokuskan pada bagaimana proses relasional memengaruhi putusan pesapa atas perilaku yang diambilnya. Metode yang digunakan dalam kajian ini adalah metode deskriptif analitis dengan didukung oleh pendekatan teori Halliday. Hasil kajian memperlihatkan bahwa (1) relasi being proses verbal relasi memuat gagasan kelas dan entitas yang memicu emosi pesapa; (2) gagasan being berelasi intensif, posesif, atau situasional; (3) proses verbal relasional memuat proposisi yang merepresentasikan strategipresentasi.